Pengaruh Profitabilitas, Ukuran Perusahaan, Debt Default dan Audit Tenure terhadap Opini Audit Going Concern - Suryani, Suryani (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
Going concern audit opinion is an opinion given by an independent auditor to a company when doubts are found whether the company can maintain its business continuity in the future. This study aims to analyze the effect of profitability, company size, debt default, and audit tenure on going concern audit opinion. The population used in this study were 170 manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019 by using the purposive sampling method, obtained a sample of 43 companies that have met the sample selection criteria. The method of analysis used is logistic regression with a significant level of 5% (0.05) and using an analysis tool in the form of SPSS version 20.0. The results showed that profitability and firm size had a negative effect on going concern audit opinion, debt default had a positive effect on going concern audit opinion, while audit tenure had no effect on going concern audit opinion.